Phase‐Field Simulations of the Morphology Formation in Evaporating Crystalline Multicomponent Films. Issue 10 (28th July 2022) - Ronsin, Olivier J. J.; Harting, Jens
Abstract: In numerous solution‐processed thin films, a complex morphology resulting from liquid–liquid phase separation (LLPS) or from polycrystallization arises during the drying or subsequent processing steps. The morphology has a strong influence on the performance of the final device but unfortunately, the process–structure relationship is often poorly and only qualitatively understood. This is because many different physical mechanisms (miscibility, evaporation, crystallization, diffusion, and advection) are active at potentially different time scales and because the kinetics plays a crucial role: the morphology develops until it is kinetically quenched far from equilibrium. In order to unravel the various possible structure formation pathways, a unified theoretical framework that takes into account all these physical phenomena is proposed. This phase‐field simulation tool is based on the Cahn–Hilliard equations for diffusion and the Allen–Cahn equation for crystallization and evaporation, which are coupled to the equations for the dynamics of the fluid. The behavior of the coupled model based on simple test cases is discussed and verified. Furthermore, how this framework allows to investigate the morphology formation in a drying film undergoing evaporation‐induced LLPS and crystallization, which is typically a situation encountered, is illustrated, for example, in organic photovoltaics applications. Abstract : A coupled phase‐field‐fluid dynamics framework is developed to simulate morphology formation of multicomponent crystalline thin films upon drying. The behavior of the coupled model is verified. Simulations of the morphology formation in a ternary drying film undergoing evaporation‐induced liquid–liquid phase separation and crystallization are presented for various structure formation pathways, depending on the mixture thermodynamic and kinetic properties.